2014
DOI: 10.1093/nar/gku417
|View full text |Cite
|
Sign up to set email alerts
|

Human AP endonuclease inefficiently removes abasic sites within G4 structures compared to duplex DNA

Abstract: Excision repair processes are essential to maintain genome stability. A decrease in efficiency and fidelity of these pathways at regions of the genome that can assume non-canonical DNA structures has been proposed as a possible mechanism to explain the increased mutagenesis and consequent diseased state frequently associated with these sites. Here we describe the development of a FRET-based approach to monitor the presence of G quadruplex (G4) DNA, a non-canonical DNA structure formed in runs of guanines, in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 49 publications
9
46
0
Order By: Relevance
“…S4). Lastly, the AP is strongly bound by APE1 in a G-quadruplex fold, but the cleavage kinetics are attenuated, as previously described 21 .…”
Section: Resultssupporting
confidence: 55%
“…S4). Lastly, the AP is strongly bound by APE1 in a G-quadruplex fold, but the cleavage kinetics are attenuated, as previously described 21 .…”
Section: Resultssupporting
confidence: 55%
“…laboratory and others, and it was found that APE1 binds APs in G4s, but the cleavage rate was highly attenuated (12,19). The attenuated cleavage by APE1 on the promoter may provide the trigger to increase the rate of transcription observed by allowing APE1 to idle on the G4/G5 structural motif.…”
Section: Significancementioning
confidence: 94%
“…The G-quadruplex fold is favored because the 5 th G track allows extrusion of the damaged G run into a large loop while maintaining the fold. The AP site is then presented to APE1 and bound by this protein; consequently, the reaction kinetics are highly attenuated by the G4 structure prolonging APE1 binding [42] and aiding in the possible recruitment of other activating transcription factors for gene induction (e.g., HIF1-α) [13]. These initial studies identify an intertwining of G oxidation in PQS elements to provide a structural switch for recruitment of BER proteins to activate transcription (Fig.…”
Section: Og Activates Mrna Synthesis By Facilitating Promoter G-qumentioning
confidence: 99%